Cloze Tests: An Integrative Approach (Journal of the College of Basic Education, 2022)
One of the axioms of language testing is that the purpose of a test affects the nature of that test, i.e., if the evaluators are after the development of conscious knowledge of grammatical structures and vocabulary items, they have to use discrete-point approach to testing. But if they are after the development of the language skills the learners need when they use the target language in real transactional situations at home or overseas, then they have to adopt integrative approach to language testing.